Risikomanagement in landwirtschaftlichen Betrieben: Eine Analyse der Akzeptanz von Wetterversicherungen mit Hilfe von Discrete-Choice-Experimenten : an analysis of the acceptance of weather insurance using discrete choice experiments; Risk Management on Farms: An Analysis of the Acceptance of Weather Insurance using Discrete Choice Experiments - Ulf Liebe; Syster Christin Maart; Oliver Mußhoff; Philipp Stubbe (German Journal of Agricultural Economics (GJAE), 2012)
– The question of how the increasing challenges of on-farm risk management - that e.g. result from the global climate change - could be met, has been an important subject of research for a long time. For instance, it has been discussed if index-based insurance are an alternative to classical hedging opportunities of weather risks. While science have mainly focused on the conception, pricing and hedging effectiveness of new weather risk management instruments, a research gap exists regarding the farmers' subjective perception of weather risks, the analysis of implemented on-farm measures for weather risk reduction as well as regarding the measurement of farmers' preferences for different risk management instruments. On the basis of survey data, this study investigates which meteorological events farmers perceive as very risky, which measures they already apply to reduce the risk and which costs are involved. Using a discrete choice experiment, beside the demand for weather insurance also the influence of performance defining features of different insurance on their selection probability is determined. Results show that farmers often are not able to quantify the costs of the risk management instruments applied so far. Even given high basis risks, they would, therefore, demand for yield insurance as well as index-based insurance if those are sold at a favorable price. Moreover, results show that the demand for insurance rises with increasing risk involvement of the agricultural enterprises as well as - against all expectations - with decreasing risk aversion of the decision makers.
Keywords: 330; Wetter; Risiko; Elementarschadenversicherung; Risikomanagement; Landwirtschaft; Diskrete Entscheidung; Experiment